Playful Learning at Home: Developing SISEMO Flashcards to Enrich Parent-Child Sensory-Motor Activities - Rani Dwi Kurniawati; Lilis Suryani (Atfaluna: Journal of Islamic Early Childhood Education, 2025)
This study aims to develop a flashcard-based, play-oriented learning medium to stimulate children's sensory-motor development through parental guidance at home. The study employed a Research and Development (R&D) methodology using the ADDIE development model, comprising analysis, design, development, limited implementation, and evaluation stages. The analysis stage involved interviews and observations to identify parents' needs in facilitating children's play activities at home. In contrast, the design and development stages focused on conceptualizing and producing the flashcard product. The research participants were parents of children aged 4–5 years (Class A) at PAUD Al-Hidayah, North Jakarta, who were directly involved in accompanying their children's play activities and sensory-motor stimulation at home. Product validation was conducted by content experts, media experts, and early childhood education practitioners using feasibility questionnaires, followed by three stages of product trials: individual, small-group, and large-group. The results indicate that the developed flashcard, named SISEMO, was classified as highly feasible, achieving validation scores of 95% from content experts, 98% from media experts, and 98% from practitioners, while the limited implementation stage yielded a positive response rate of 87.80%. The study focuses on the development of sensory-motor flashcards that include structured, practical play-based activity ideas for collaborative parent–child use at home, thereby bridging early childhood developmental stimulation between school and family environments. This study concludes that the SISEMO Flashcard is both practical and feasible as a supportive medium for parents' sensory-motor play activities. Future research is recommended to examine the effectiveness of this product using experimental designs with control groups and to extend its implementation across diverse social and cultural contexts to strengthen the generalizability of the findings.